LOCAL WISDOM-BASED TOURISM THEATRE: A COMMUNITY EMPOWERMENT MODEL FOR CULTURAL PRESERVATION - Ni Made Ruastiti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Local wisdom is a cultural resource rich in aesthetic, social, and spiritual values, as well as serving as a community's collective identity. In the context of tourism, local wisdom has great potential to be developed into tourist theater that not only provides entertainment but also conveys authentic cultural narratives. The urgency of this research stems from the need to develop a tourist theater model capable of empowering local communities as key actors, so that the preservation of traditions can go hand in hand with strengthening the creative economy. This research aims to formulate a tourist theater management model based on local wisdom by involving the community, identifying strategies for maintaining cultural values, and measuring its impact on socio-cultural sustainability. The issues raised include formulating a tourist theater concept based on local values, community empowerment strategies, and indicators of successful cultural preservation in the tourism context. This research uses qualitative ethnographic methods through participant observation, in-depth interviews, and documentation analysis, supported by focus group discussions with artists, traditional leaders, and tourism managers. The results show that tourist theater based on local wisdom is effective in building collective awareness, strengthening cultural identity, and increasing community income. The integration of traditional narrative elements, performance aesthetics, and participatory management is key to the success of this model. The novelty of this research lies in the development of a community-based tourism theater model that combines ethnoaesthetics and community-based tourism theories, resulting in a conceptual and practical framework that can be replicated in various areas with cultural tourism potential in Indonesia.